Cabotegravir long acting injection protects macaques against intravenous challenge with SIVmac251. (20th February 2017) - Andrews, Chasity D.; Bernard, Leslie St.; Poon, Amanda Yee; Mohri, Hiroshi; Gettie, Natanya; Spreen, William R.; Gettie, Agegnehu; Russell-Lodrigue, Kasi; Blanchard, James; Hong, Zhi; Ho, David D.; Markowitz, Martin
Abstract : Objective: We evaluated the effectiveness of cabotegravir (CAB; GSK1265744 or GSK744) long acting as preexposure prophylaxis (PrEP) against intravenous simian immunodeficiency virus (SIV) challenge in a model that mimics blood transfusions based on the per-act probability of infection. Design: CAB long acting is an integrase strand transfer inhibitor formulated as a 200 mg/ml injectable nanoparticle suspension that is an effective PrEP agent against rectal and vaginal simian/human immunodeficiency virus transmission in macaques. Methods: Three groups of rhesus macaques ( n  = 8 per group) were injected intramuscularly with CAB long acting and challenged intravenously with 17 animal infectious dose 50% SIVmac251 on week 2. Group 1 was injected with 50 mg/kg on week 0 and 4 to evaluate the protective efficacy of the CAB long-acting dose used in macaque studies mimicking sexual transmission. Group 2 was injected with 50 mg/kg on week 0 to evaluate the necessity of the second injection of CAB long acting for protection against intravenous challenge. Group 3 was injected with 25 mg/kg on week 0 and 50 mg/kg on week 4 to correlate CAB plasma concentrations at the time of challenge with protection. Five additional macaques remained untreated as controls. Results: CAB long acting was highly protective with 21 of the 24 CAB long-acting-treated macaques remaining aviremic, resulting in 88% protection. The plasma CAB concentration at the time of virus challenge appeared to be more important for protection than sustaining therapeutic plasma concentrations with the second CAB long acting injection. Conclusion: These results support the clinical investigation of CAB long acting as PrEP in people who inject drugs. Abstract : Supplemental Digital Content is available in the text